2020
DOI: 10.1590/0037-8682-0388-2019
|View full text |Cite
|
Sign up to set email alerts
|

Association of leptin and leptin receptor polymorphisms with coronary artery disease in a North Chinese Han population

Abstract: Introduction: Leptin (LEP) is a peptide hormone that acts via leptin receptor (LEPR) binding. Genetic evidence from different human populations has implicated LEP/LEPR in the pathogenesis of coronary artery disease (CAD), and suggests that certain LEP/LEPR gene polymorphisms may increase the risk of CAD. The aim of this study was to assess two single nucleotide polymorphisms (SNPs) in LEP genes (rs2167270 and rs7799039) and two in LEPR genes (rs6588147, rs1137100) for association with CAD. Methods: We enrolled… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 20 publications
0
7
0
Order By: Relevance
“…COVID-19 is currently being treated with some anti-infective drugs, such as antiviral drugs [ 10 ], antimalarial drugs [ 11 ], and immunosuppressive drugs [ 12 ]. However, the effectiveness of these drugs in treating patients with SARS-CoV-2 has not been approved yet [ 13 ]. Several synthetic compounds have recently been suggested to inhibit ACE2 by binding with the amino acid residues that are involved in direct interaction with the viral receptor-binding domain (RBD).…”
Section: Introductionmentioning
confidence: 99%
“…COVID-19 is currently being treated with some anti-infective drugs, such as antiviral drugs [ 10 ], antimalarial drugs [ 11 ], and immunosuppressive drugs [ 12 ]. However, the effectiveness of these drugs in treating patients with SARS-CoV-2 has not been approved yet [ 13 ]. Several synthetic compounds have recently been suggested to inhibit ACE2 by binding with the amino acid residues that are involved in direct interaction with the viral receptor-binding domain (RBD).…”
Section: Introductionmentioning
confidence: 99%
“…All of these controversial findings are not well elucidated in the literature. The different findings may possibly be a result of diversity in the genetic background of the populations, or interactions with other pathways of leptin or leptin receptors ( 24 ) , in addition to there being a possible influence of this risk allele on the presence of metabolic syndrome ( 25 ) or even cardiovascular events such as heart attack ( 26 ) .…”
Section: Discussionmentioning
confidence: 99%
“…Many studies report associations between leptin/leptin receptor interactions and CAD. Wang et al conducted a study evaluating single nucleotide polymorphisms (SNPs) in leptin genes and leptin receptor (LEPR) genes [ 37 ]. The study aimed to uncover associations between different SNPs and CAD.…”
Section: Reviewmentioning
confidence: 99%
“…A total of 384 North Chinese Han individuals were enrolled in the study, where 217 were patients diagnosed with CAD and 113 were healthy subjects. The results showed that: genetic variations at leptin rs7799039 and rs2167270 convey an increased risk of CAD in the northern Chinese population, and leptin rs2167270 and rs7799039 gene polymorphisms might affect predisposed individuals within the North Chinese population to CAD [ 37 ].…”
Section: Reviewmentioning
confidence: 99%